(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Lyudmila P. Gromova, Olga I. Lepilkina, Vladimir V. Tulupov (St. Petersburg, Stavropol, Voronezh, Russian Federation) Evgeny Akhmadulin – grand Ph.D. of Philology, Professor, headed the Department of Theory of Journalism of Rostov State University, and then Southern Federal University for many years. Chairman of the South-Russian educational-methodical association in journalism. Full member of the Academy of Sciences of the regional press of Russia, corresponding member of the Peter the Great Academy of Sciences and Arts. The author of ten monographs, three textbooks on the history and theory of journalism and more than 200 scientific articles. This scientific review is devoted to his multifaceted research in the field of history and theory of journalism. It includes a review of the methodology of retrospective studies, the concepts of periodization, the application of the systems approach, the principles of historicism and typological methods in the analysis of historical trends and metamorphoses that occurred in Russian journalism during the most difficult period of its operation. His works gave impetus to the formation of research schools of journalistic regional studies in the republics of the North Caucasus, Kuban, Stavropol region and Astrakhan. His main achievement in theoretical studies is the phenomenon of journalism as an integrated system. It gives a model representation of the processes of mass communication occurring in the journalism system, and this kind of “simulator” shows the role, tasks and functions of journalism as a whole, its subsystems and individual components. Key words: region, press, history of journalism, typology, press of political parties, system of journalism, system-forming factors, models of mass communication, functions of journalism. DOI 10.23683/1995-0640-2019-2-191-200